The Role of the Media in Promoting Human Rights in Pakistan: Significance and Challenges - Dr.M.Qadeer , Muhammad faisal , Ajazuddin, Asifa Azam (International Research Journal of Arabic and Islamic Studies, 2022)
The media also very importantly performs in developing countries like Pakistan where human rights are vulnerable to violations, on one hand by shaping public discourse and on the other, to accountability and safeguards democratic values. As this article intends to be a critical appraisal of media’s contribution (or lack thereof) to rights promotion in Pakistan, it tries to answer the question of how badly needed, how well is the media doing it and what are the myriad problems of ability (or inability as the case might) to do it. Since long in Pakistan, Pakistan is a phenomenon where media has done the two roles of the watchdog and the voice of the voiceless. It has used its compelling investigative journalism, on the ground reporting filled with advocacy campaigns to expose the likes of gender based violence, minority rights and enforced disappearance, freedom of expression. At the same time, it has placed it forward as an intermediary between civil society and the state and has enlarged the voices of human rights defenders and victims when their voices would be muffled. This is neither a straight line nor has it no limits as far as the media’s role in promoting human rights. Not only is it controlled by equally complex medleys of political pressure, legal restrictions, economic dependency, and security concerns, but also the Pakistani media. Censorship, threats of intimidation, actual intimidation (including being brutalised) are repeatedly applied against the press when dealing with military operations, religious extremism, state abuses. It generally works in an environment that tends to curtail journalistic freedom and prevent in depth reporting on human rights due to lack of precise laws of defamation, cybercrime and national security. Moreover, media ownership patterns, corporate interests typically affect editorial independence and thus biased or superficial treatment of human rights concerns. Social media has proven to be a phenomenal tool in human rights advocacy, but with such comes digital surveillance, misinformation, vhatash and what new challenges it presents when human rights advocacy is advanced in the digital age. In such circumstances, the media play an indispensable role in the development of the Pakistani human rights landscape. The rise and collaboration of these outlets and the opening of spaces to engage with civil society have created increasingly increasing spaces. Internationally, partnerships have also been built to train media resilience via training programs — capacity added in the face of adversity including media capacity. If media is to make a positive contribution to human rights promotion in Pakistan, this paper believes that, in order for legal reform in the interests of press freedom to take place, investigative journalism can be better institutionally supported, and media literacy can be developed amongst the community. Additionally, this will also guarantee that all segments of society; especially those who are disadvantaged are duly and actually reflected in an environment of ethical journalism and pluralistic narratives. This article argues to provide a deeper understanding of the relations between structure, operation and media’s role in Pakistan and their role in Pakistan in order to analyze the intersection of media and human rights in order to recommend policy suggestions on how to strengthen Pakistan’s capability and functions as a human rights watch dog(Fox & Saunders, 2024).